2010
DOI: 10.1002/jbmr.133
|View full text |Cite|
|
Sign up to set email alerts
|

Insulin-like growth factor 2 (IGF-2) potentiates BMP-9-induced osteogenic differentiation and bone formation

Abstract: Efficient osteogenic differentiation and bone formation from mesenchymal stem cells (MSCs) should have clinical applications in treating nonunion fracture healing. MSCs are adherent bone marrow stromal cells that can self-renew and differentiate into osteogenic, chondrogenic, adipogenic, and myogenic lineages. We have identified bone morphogenetic protein 9 (BMP-9) as one of the most osteogenic BMPs. Here we investigate the effect of insulin-like growth factor 2 (IGF-2) on BMP-9-induced bone formation. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
251
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 228 publications
(259 citation statements)
references
References 74 publications
6
251
1
1
Order By: Relevance
“…Mechanistically, IGF-2 is further shown to enhance the BMP-9-induced BMPR-Smad reporter activity and Smad1/5/8 nuclear translocation. PI3-kinase (PI3K) inhibitor LY294002 abolishes the IGF-2 potentiation effect on BMP-9-mediated osteogenic signaling and can directly inhibit BMP-9 activity [16]. Consistent with these results, we observed that p-Erk1/2 and p-Smad1/5/8 levels were significantly decreased in IGFBP4-overexpressed MSCs and increased in IGFBP4 knockdown cells in the presence of BMP2.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Mechanistically, IGF-2 is further shown to enhance the BMP-9-induced BMPR-Smad reporter activity and Smad1/5/8 nuclear translocation. PI3-kinase (PI3K) inhibitor LY294002 abolishes the IGF-2 potentiation effect on BMP-9-mediated osteogenic signaling and can directly inhibit BMP-9 activity [16]. Consistent with these results, we observed that p-Erk1/2 and p-Smad1/5/8 levels were significantly decreased in IGFBP4-overexpressed MSCs and increased in IGFBP4 knockdown cells in the presence of BMP2.…”
Section: Discussionsupporting
confidence: 78%
“…Serum levels of IGFBP4 showed negative correlation with calcaneal bone mineral density among post-menopausal SouthIndian women [15]. Importantly, expression of IGFBP4 inhibits BMP-9-induced ALP activity and matrix mineralization in MSCs [16], suggesting that IGFBP4 is involved in the osteogenic potency of MSCs.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Matrix mineralization nodules usually emerge at 10 days and reach peaks at 17-20 days after induction (19). TGFβ1 alone had no difference with AdGFP control that corresponded with ALP activity, indicating that TGFβ1 itself is unable to induce osteogenesis in MSCs (20), while small mineralized nodules were visible in the group treated with AdBMP9 in combination with 5 ng/ml or 10 ng/ml TGFβ1 at day 5 whereas AdBMP9 alone exhibited apparent nodules at day 13 ( Fig.…”
Section: Effect Of Tgfβ1 On Bmp9-induced Matrix Mineralization In C3hmentioning
confidence: 90%
“…There are two types, IGF-1 and IGF-2, which play a wide variety of cellular roles from the regulation of proliferation to apoptosis. Both IGF-1 and IGF-2 have been shown to be associated with increase in bone formation and density (Adami et al 2010, Chen et al, 2010 while their reduction has been shown to be associated with decreased bone density (Bennett, 1984). In order to specifically identify genes upregulated during osteogenesis, our group isolated RNA from human adipose-derived stromal cells during in-vitro osteogenesis and performed a microarray analysis (Lee, Longaker, 2010).…”
Section: Tissue Engineering For Tissue and Organ Regeneration 114mentioning
confidence: 99%